الصناعة المعجمية و نظرية النحت العربية قراءة في كتاب:(المعجمية :مقدمة نظرية و مطبّقة/مصطلحاتها و مفاهيمها للحمزاوي أنموذجا) - ملال, وهيبة (جامعة الوادي - university of Eloued, 2020)
المعجم المتخصص هو الذي يتضمّن مصطلحات علم معين و يختص بهاو نظرا لأهميته سارع كثير من المعجميين إلى الاهتمام بالصناعة المعجمية و الفعل المصطلحي، و التركيز على قضية جمع ووضع المصطلح المتخصص. من بين هؤلاء "محمد رشاد الحمزاوي" وهو من ثلّة الباحثين الذين أثْروا حقل الصناعة المعجمية على مستوى التنظير و التطبيق بهدف إرساء أسس المعجم النموذج و تصوّر ذهنية معجمية عربية ذات طابع عالمي. على هذا الأساس جاءت هذه الورقة البحثية الموسومة ب "الصناعة المعجمية ونظرية النحت العربية قراءة في كتاب: (المعجمية :مقدمة نظرية و مطبقة / مصطلحاتها و مفاهيمها للحمزاوي أنموذجا)" وهي مقاربة معجمية نظرية و مطبّقة تهدف إلى دراسة و تحليل آليات وضع المصطلحات المعجمية بغرض تثمين الجهود المعجمية العربية وصولا إلى نتائج موضوعية . : Abstract The special lexic is the one which contains concepts of another sience and intrested in it. Due to its importance a lot of linguists run to give much interest to lexical fabrication and conceptuel action and focusing on the issue of collecting and puting the special concept . One of those linguists is " Mouhamed Rachad El hamzaoui " . He is one of the few researchers who enrich the lexical fabrication in both of theoritical and applicated levels aiming at puting bases of the patterned dictionary and trying to create an arabic lexic of an international shape . On this base comes this research paper intitled "lexical fabrication and the arabic sculpture theory reading in book( Lexic : theoritical and applicated introduction / its concepts and defenitions by El hamzaoui as a pattern). It's a theoritical and applicated . aiming at studying and analyzing mechanisms for creating a lexical concepts in order to appreciate the arabic lexical efforts to reach objective results.
مقال
Keywords: الصناعة المعجمية؛ الفعل المصطلحي؛وضع المصطلح؛النحت; Lexical fabrication ; conceptuel action ; puting the concept ; the sculpture